Produktivitas Pekerja pada Pekerjaan Pembesian Balok pada Pembangunan Gedung Kantor PX. X di Surabaya - Malik, Ariansyah; Beatrix, Michella (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Successful construction management can be seen from the achievement in managing construction projects that are completed on time as planned. In this research project does not calculate worker productivity, there is no target for each work item, only the final target of the project and this project does not have calculations related to labor productivity, which results in an impact on the achievement of work targets. Therefore, researchers conducted research with the aim of knowing the productivity value of labor. This research was conducted at the office and house building construction project of PT X located at Jl. Komering, Darmo, Wonokromo sub-district, Surabaya. The result of the research is the value of labor productivity on the construction project of the office building and the house of PT X is classified as an effective or satisfactory category, obtained the average value of LUR on beam concreting work of 81.52% morning time and 76.33% afternoon time.